2017
DOI: 10.1002/jctb.5173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbubble diameter, alkaline concentration and temperature on reactive oxygen species concentration

Abstract: BACKGROUND In comparison with ordinary bubbles, microbubbles exhibit low floating rate and high surface charge density. More importantly, microbubbles shrink gradually and the gas–liquid interface charges congest significantly, generating large surface potential and energy, which promotes the formation of reactive oxygen species (ROS) when microbubbles eventually collapse. In this study, size‐controllable microbubbles were introduced to alkaline solutions by titanium microporous filters, and the effects of mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…(4) Temperature: The temperature also has a role in − OH generation by MNBs. Yu et al explained that in an alkaline MNB solution, the ROS concentration first increased and then decreased with the temperature rise [110]. By this effect, a parabolic trend was shown, where the ROS concentration reached its maximum at 65 • C (Figure 3E).…”
Section: Influencing Factors Of •Oh Generation In Mnbwmentioning
confidence: 82%
See 1 more Smart Citation
“…(4) Temperature: The temperature also has a role in − OH generation by MNBs. Yu et al explained that in an alkaline MNB solution, the ROS concentration first increased and then decreased with the temperature rise [110]. By this effect, a parabolic trend was shown, where the ROS concentration reached its maximum at 65 • C (Figure 3E).…”
Section: Influencing Factors Of •Oh Generation In Mnbwmentioning
confidence: 82%
“…(3) Bubble size: The bubble size also plays a crucial role in the generation of •OH by MNBs. Yu et al reported that titanium microporous filters to control the size of MNBs can be used to study the effect of their size on the concentration of reactive oxygen species (ROS) [110]. The results showed that the dependence of the ROS concentration on the size of microporous filters induced a quasi-parabolic change.…”
Section: Influencing Factors Of •Oh Generation In Mnbwmentioning
confidence: 99%
“…The physical modification significantly influences the further process of ROS generation. We rationalize that the conventional thermodynamics of the bubble collapse phenomenon led to ozone breakdown. Furthermore, this process comprises three sequential stages, namely, initiation, propagation, and termination.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that all oxygen NB suspensions prepared under various preparation conditions could produce ·OH to cause the degradation of MB, and the degradation kinetics of MB showed a common trend in all of the experimental groups, i.e., MB had a relatively rapid degradation rate in the initial stage, while the degradation rate gradually became slower thereafter. This trend may be due to the different characteristics of oxygen NBs in the suspensions prepared under different preparation conditions, such as particle size distribution, ζ-potential, and concentration, which are the determining factors for the generation rate and yield of ·OH from the collapse of oxygen NBs . The rapid destabilization of NBs is the key to the generation of ·OH, while the combined effect of the above-mentioned characteristic factors of oxygen NBs prepared under different preparation conditions will ultimately affect the stability of NBs.…”
Section: Resultsmentioning
confidence: 99%
“…This trend may be due to the different characteristics of oxygen NBs in the suspensions prepared under different preparation conditions, such as particle size distribution, ζ-potential, and concentration, which are the determining factors for the generation rate and yield of •OH from the collapse of oxygen NBs. 37 The rapid destabilization of NBs is the key to the generation of •OH, while the combined effect of the above-mentioned characteristic factors of oxygen NBs prepared under different preparation conditions will ultimately affect the stability of NBs. Thus, the common trend of the faster and then slower degradation rate is caused by the difference in the amount of • OH exposure triggered by the collapse of bubbles with different properties.…”
Section: ■ Results and Discussionmentioning
confidence: 99%